(untitled) (Journal of International Studies, 2018)
Indonesia is a country that is inhabited by hundreds of ethnic groups with different geographical condition, natural resources and social culture. Regional decentralization and autonomy that is carried out in Indonesia is an acknowledgment of ethnic diversity (pluralism) to create unity and harmony (BhinekaTunggal Ika), to form social harmony and equal development with the framework of protecting national stability. This article argues on the urgency of political decentralization and regional autonomy in Indonesia through local perspectives by using political decentralization/local democracy model approach with the centrifugal style of authority and government decentralization and structural efficiency model approach with centripetal style.